Successfully disseminating and exploiting project results and products of strategic partnerships : handbook - Dunkel, Torsten [Herausgeber]; Dreissus-Meurer, Sigrid [Herausgeber] (My University, 2019)
This handbook is intended primarily for project coordinators and project partners of the strategic partnerships key action (KA2) as they hold key positions in terms of the dissemination and exploitation of product and project results. However, it might also be of interest and helpful to other project leaders in Erasmus+, e.g. those implementing mobility projects (KA1). It contains:the description of key elements of the dissemination process, consolidated with visual prompts; helpful recommendations and practical tips for designing and implementing effective dissemination and for ensuring the exploitation and sustainability of your projects, e.g. by conducting an impact assessment and creating OER licences; good practice examples to illustrate the information; an appendix containing templates and a glossary of key terms. (excerpt; BIBB-Doku)
Keywords: I 1.4 Berufsbildungsprojekte/Entwicklungsprojekte; I 2.2 Europa; EU-Programm; Erasmus plus; Transfer